AN ANALYSIS OF READING MATERIALS IN PATHWAY TO ENGLISH AN ENGLISH TEXTBOOK FOR THE TENTH GRADE SENIOR HIGH SCHOOL - Handayani, Fitri (RC-INSTITUT, 2019)
A material in a textbook has to fit with the curriculum, syllabus, and students’ background of knowledge, aims and the goal of teaching learning process itself.Thats why this research is important to be conducted. The data collected for this study gathered from the English textbook Pathway to English published by Erlangga. The data were in the form of reading material or reading passages provided in the textbook. The objectives of this research is to discover whether the Pathway to English textbook has fulfilled the criteria of good reading material based on Hetherington’s reading evaluation criteria. The result findings of this research showed thatalmost all criteria of good reading materials from Hetherington are fulfilled by Pathway to English Textbook. Based on the findings of this study the researcher suggested that teachers and educational institution should pay attention more with the content of the textbook and its relevance with the curriculum and appropriate with the students’ need.